2011
DOI: 10.1021/cs2003774
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Decomposition of Aqueous Hydrogen Peroxide over Heterogeneous TiSBA15 and TS-1 Selective Oxidation Catalysts: Insights from Spectroscopic and Density Functional Theory Studies

Abstract: The Ti-based heterogeneous catalysts TiSBA15, Bu cap TiSBA15, TS-1, and [Ti,Al]-MFI were investigated with respect to controlling factors for the competitive decomposition of aqueous H2O2 during selective catalytic oxidations. DRUV–vis spectroscopy revealed that the titanium species in these materials exist mainly in isolated, tetrahedral coordination environments. The observed rates of H2O2 decomposition at 65 °C in acetonitrile decreased in the following order: Bu cap TiSBA15 > TiSBA15 and TS-1 > [Ti,Al]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 65 publications
12
84
1
Order By: Relevance
“…Whilst ICP analysis also revealed a decrease in trace Fe content following etching (Fe content decreased from 326 to 254 ppm), control measurements investigating the ability of Fe-silicalite-1 to decompose H2O2 revealed that the impurity Fe content was not responsible for H2O2 decomposition (ESI Table S3). The inability of this MFI material to catalyse H2O2 decomposition at a similar Fe loading to that found in TS-1 as impurities clearly indicates that Ti is required for decomposition to proceed, in good agreement with previous studies [18]. Accordingly, we re-focused our attention on spectroscopic study of the Ti active sites with more sensitive spectroscopic techniques.…”
Section: Spectroscopic Studies With In Situ Ramansupporting
confidence: 86%
See 1 more Smart Citation
“…Whilst ICP analysis also revealed a decrease in trace Fe content following etching (Fe content decreased from 326 to 254 ppm), control measurements investigating the ability of Fe-silicalite-1 to decompose H2O2 revealed that the impurity Fe content was not responsible for H2O2 decomposition (ESI Table S3). The inability of this MFI material to catalyse H2O2 decomposition at a similar Fe loading to that found in TS-1 as impurities clearly indicates that Ti is required for decomposition to proceed, in good agreement with previous studies [18]. Accordingly, we re-focused our attention on spectroscopic study of the Ti active sites with more sensitive spectroscopic techniques.…”
Section: Spectroscopic Studies With In Situ Ramansupporting
confidence: 86%
“…Although the treatment of various zeolites with NH4HF2 has been found to induce some mesopores formation [17], the impact of this was ruled out given the negligible changes observed in the porosimetry data (Table S1). Similarly, changes to the potential acid/base character of TS-1-an important factor in H2O2 decomposition chemistry [18]-were also ruled out, based on previous observations that NH4HF2 treatment does not change surface acidity (neither Lewis nor Brønsted) to any extent [17]. Fluorine analysis of TS-1B revealed that no residual fluorine remained after treatment (Table S2), and thus changes to the hydrophilicity or polarity of the catalyst based on fluorine are unlikely.…”
Section: Spectroscopic Studies With In Situ Ramanmentioning
confidence: 99%
“…PPA is a known poison for TiO x –SiO 2 catalysts, but has not been used previously for the quantitative determination of active sites 7a. 17…”
Section: Resultsmentioning
confidence: 99%
“…Tetrahedrally coordinated titanium, which is called framework Ti, is usually considered as the active center for the oxidation reactions. 11 Moreover, anatase TiO 2 can even lead to decomposition of hydrogen peroxide. 10 This 5MR, which was reported by Clerici et al, can oxidize propene to prepare propene oxide.…”
Section: Introductionmentioning
confidence: 99%